1999
DOI: 10.1037/0090-5550.44.3.248
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of adult learning disability subtypes in the vocational rehabilitation system.

Abstract: To examine the personal adjustment and vocational outcomes of adults with different subtypes of specific learning disabilities. Design: Cluster analysis was used to derive subtypes from a vocational rehabilitation population, and nonparametric tests were used to test hypotheses. Participants: Three hundred sixty-one successfully employed persons were compared with 252 unsuccessfully employed persons. Main Outcome Measures: Rates of secondary psychiatric disorders, type of training, and category of vocational a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Seventy-four percent had experienced working since leaving secondary school and the majority of them worked in competitive employment. While this number appeared encouraging and comparable to findings from overseas [45,46], the fact is that this rate is perceived as disappointing when compared to their peers without disabilities [47]. With the exception of studies by Madaus [7,48], most overseas studies reported unsatisfactory employment outcomes of school leavers with LD.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Seventy-four percent had experienced working since leaving secondary school and the majority of them worked in competitive employment. While this number appeared encouraging and comparable to findings from overseas [45,46], the fact is that this rate is perceived as disappointing when compared to their peers without disabilities [47]. With the exception of studies by Madaus [7,48], most overseas studies reported unsatisfactory employment outcomes of school leavers with LD.…”
Section: Discussionsupporting
confidence: 70%
“…Findings from this study support the recommendation to provide vocational rehabilitation programs for young adults with LD who require more comprehensive training courses [1,2,28,47]. The training program should incorporate other necessary skills, such as social skills training, living skills training, and survival skills training, and follow up services that were found to be important for successful employment.…”
Section: Recommendationssupporting
confidence: 61%
“…The individuals provided with college training may have lacked academic skills and cognitive ability to compete at the college level, or they may not have been provided sufficient support services and accommodations, commensurate with their functional limitations. With regard to support services, Dunham, Multon, and Koller [10] stated that individuals receiving postsecondary training may not receive or may not take advantage of appropriate accommodations. This finding is similar to the Dunham, Koller, and Mclntosh [9] study, which found that college training negatively correlated with successful closure.…”
Section: Specific Learning Disability In Vocational Rehabilitation Comentioning
confidence: 99%
“…Previous work has repeatedly shown that adults with LD commonly fail to graduate high school (Adelman & Vogel, 1990). It would appear that adults with seizure disorders from childhood are very much like them, and likely are at risk for the same kinds of poor vocational futures that often characterize individuals with LD (Dunham et al, 1999;Spekman, Goldberg, & Herman, 1992).…”
Section: Discussionmentioning
confidence: 95%
“…Like persons with symptomatic epilepsy, those with idiopathic seizures are at risk for the development of learning disorders, associated school problems, and later vocational challenges (Dunham, Multon, & Koller, 1999;Paradiso et al, 2001). This study was also able to show that even in cases when the diagnostic criteria of LD were not fully met, the group of adults with seizures performed much more closely akin to those with LD than to adults with physical disabilities.…”
Section: Discussionmentioning
confidence: 98%